${{12} \over {3 + \sqrt 5 - 2\sqrt 2 }} = $

  • A

    $1 + \sqrt 5 + \sqrt {(10)} + \sqrt 2 $

  • B

    $1 + \sqrt 5 - \sqrt {(10)} + \sqrt 2 $

  • C

    $1 + \sqrt 5 + \sqrt {10} - \sqrt 2 $

  • D

    $1 - \sqrt 5 - \sqrt 2 + \sqrt {(10)} $

Similar Questions

${{3\sqrt 2 } \over {\sqrt 6 + \sqrt 3 }} - {{4\sqrt 3 } \over {\sqrt 6 + \sqrt 2 }} + {{\sqrt 6 } \over {\sqrt 3 + \sqrt 2 }} = $

જો ${\left( {{2 \over 3}} \right)^{x + 2}} = {\left( {{3 \over 2}} \right)^{2 - 2x}},$ તો $x =$

જો ${x^{x\root 3 \of x }} = {(x\,.\,\root 3 \of x )^x},$ તો $x = .. . .$

${{15} \over {\sqrt {10} + \sqrt {20} + \sqrt {40} - \sqrt 5 - \sqrt {80} }} = . . . $

$\sqrt {(3 + \sqrt 5 )}  = . .$ .